Using Twitter in Ukrainian sociology majors training - Liubov F. Panchenko; Andrii O. Khomiak; Andrey V. Pikilnyak (Academy of Cognitive and Natural Sciences, 2020)
The article deals with the problem of using cloud technologies in the training of sociology students in Ukraine. The popularity of Twitter in Ukraine is analyzed. The possibilities of using Twitter as a learning tool in classroom are discussed. List of recommended tweeters, including Ukrainian resources as well as resources related to population censuses is proposed. The article offers examples of student activities for Social Statistics and Demographics courses. The article demonstrates that new forms of student's activity related to data analysis introduced by academics and practitioners (building art objects and storytelling based on data; shared data collection by citizens through mobile devices, "play with data" modern data visualization services) can be realized with Twitter resources and can help overcome the barriers that arise while studying quantitative methods.